Analysis of the Relationship Between Online Shopping Experience, Service Quality and Online Shopping Satisfaction on Repurchase Intention in Tokopedia - Larasati Ayu Sekarsari; Farakh Wakhidah (Islamic University of Kalimantan MAB Banjarmasin, 2024)
This research examines the relationship between online shopping experience, service quality and online shopping satisfaction on repurchase intentions at Tokopedia. The type of research used is quantitative research using a consumer survey approach. The sampling technique used was purposive sampling. Data collection was carried out using a survey method via a Google form which was filled in by respondents. The research sample used was 210 respondents who had shopped at Tokopedia. In this research, the test used in statistical analysis is hypothesis testing with Smart PLS software. Based on the processing results, (1) online shopping experience has a significant effect on online shopping satisfaction; (2) service quality has a significant effect on online shopping satisfaction: and (3) online shopping satisfaction has a significant effect on repurchase intention.